The journal Nuklearmedizin - Lerch, H.; Jigalin, A. (Nuklearmedizin - NuclearMedicine, 2003)
Aim and Method: The scientific publications in the 2001 and 2002 issues of the journal Nuklearmedizin. Journal of Functional and Molecular Imaging were analyzed retrospectively with regard to molecular imaging/therapy content criteria. Results: Out of a total of 82 original papers and case reports 83% were based on molecular or functional methods, 91% of them using commercially available tracers, 57% were categorized as molecular imaging, 11% as molecular therapy, 12% as functional imaging and 2% as functional therapy. 3% of the studies were categorized as experimental research. Researchers from medical specialities other than nuclear medicine were co-authors in 71% of the articles, they were rooted in basic medical sciences in 16%. Of the 65 original papers 51% were predominantly dedicated to methodological development; 49% of them were prospective studies. Conclusion: The subtitle Journal of Functional and Molecular Imaging describes the current practice of publishing in Nuklearmedizin. The number of authors from other specialities shows that multidisciplinar integration within the field of molecular imaging is performed. Nevertheless, more integration of basic medical sciences is needed. Nuklearmedizin contributes to the insight of molecular imaging and to its clinical application in humans.
Keywords: Scientific publishing; nuclear medicine; molecular imaging